TSESEVICH AND KRAKOW’S ASTRONOMERS - Flin, P. (Одеські астрономічні публікації, 2007)
In the paper I present some aspects of collaboration between Prof. Vladimir Platonovich Tsessevich and Cracow’s astronomers working in the field of variables stars.